The relationship between clinical characteristics including presence of exposed lesions and health‐related quality of life (HRQoL) in patients with psoriasis: analysis from the nationwide epidemiologic study for psoriasis in Korea (EPI‐PSODE study). (5th March 2018) - Youn, S.W.; Lee, J.‐H.; Yu, D.Y.; Kim, Y.; Kim, B.S.; Seo, S.J.; Choe, Y.B.; Yun, S.‐K.; Park, J.; Kim, N.I.; Choi, C.W.; Youn, J.I.; et al.
Abstract: Background: Psychological aspect and quality of life should be considered in treating patients with psoriasis. Objective: We sought to ascertain which clinical characteristics including presence of exposed lesions are associated with impairment of health‐related quality of life (HRQoL) in patients with psoriasis. Methods: The EPI‐PSODE study was a nationwide, multicenter, cross‐sectional study conducted in Korea that included 1260 adult patients with psoriasis. In addition to clinical characteristics including presence of exposed lesions, data were collected using the Psoriatic Arthritis (PsA) Screening and Evaluation (PASE), Dermatology Life Quality Index (DLQI), MOS 36‐Item Short‐Form Health Survey (SF‐36), Work Productivity and Activity Impairment Questionnaire Psoriasis (WPAI: PSO) and Medication Satisfaction Questionnaire (MSQ). Results: Patients with a DLQI score > 5 ( n  = 990) were younger, had an earlier onset of psoriasis, scored higher on the Psoriasis Area and Severity Index (PASI), had higher body surface area (BSA) and had higher PASE scores than patients with DLQI ≤ 5 ( n  = 266). The group of patients with exposed lesions ( n  = 871) were younger and male predominance, earlier onset of psoriasis, longer disease duration, higher PASI/BSA score and a higher proportion with drinking and smoking history each than the group of patients without exposed lesions ( n  = 389). Presence of exposed lesions negatively influenced DLQI, 36‐Item Short‐Form Health Survey (SF‐36) (mental component), presenteeism, total work productivity impairment and total activity impairment in the WPAI: PSO. In multiple regression model, PASI score was the only variable which was significantly associated with all HRQoL measures. Presence of exposed lesions was a significant factor affecting DLQI and SF‐36 (mental). Conclusion: The presence of exposed lesions has a negative impact on quality of life, mental health and work productivity. Therefore, effective treatments are particularly needed for psoriasis patients with exposed lesions.